Correction: The Western Corn Rootworm is Strongly Attracted to Floral (E)-p-Methoxycinnamaldehyde, but not or Weakly to other Compounds of the oil Pumpkin - Martin Schlager; Stephan Manhalter; Katharina Wechselberger; Zsolt Kárpáti; Stefan Dötterl (Journal of Chemical Ecology, 2026)

The Western Corn Rootworm is Strongly Attracted to Floral (E)-p-Methoxycinnamaldehyde, but Not or Weakly to Other Compounds of the Oil Pumpkin - Martin Schlager; Stephan Manhalter; Katharina Wechselberger; Zsolt Kárpáti; Stefan Dötterl (Journal of Chemical Ecology, 2026)
The western corn rootworm (WCR, Diabrotica virgifera virgifera) is one of the most serious pests in maize. In some parts of Europe, maize is frequently cultivated adjacent to the Styrian oil pumpkin ( Cucurbita pepo pepo var. styriaca ). Adult beetles are strongly attracted to the flowers of this cucurbit, likely due to their strong scent, and lay some of their eggs in the soil of the pumpkin crop. This makes crop rotation, an otherwise effective pest control strategy, less effective. Here, we used gas chromatography coupled to electroantennographic detection (GC-EAD) and field biotests to identify floral scent compounds of the oil pumpkin that elicit physiological and behavioural responses in WCR, respectively. We identified 18 non-sex specific EAD-active compounds for WCR. In field tests, 1,4-dimethoxybenzene, the main compound in pumpkin floral scent, was not attractive to WCR, whereas ( E )- p -methoxycinnamaldehyde, a minor compound, was as attractive as the complete pumpkin mixture. This research provides the basis for developing an attract and kill system, to prevent, or at least mitigate, the substantial yield losses caused by WCR.

Ni tolerance and its distinguished amelioration by chelating agents is reflected in root radius of B. napus cultivars - Humera Nawaz; Stephan Manhalter; Aamir Ali; Muhammad Yasin Ashraf; Ingeborg Lang (Protoplasma, 2019)